2019
DOI: 10.1155/2019/6178163
|View full text |Cite
|
Sign up to set email alerts
|

Lignosulfonates as Fire Retardants in Wood Flour-Based Particleboards

Abstract: Wood flour particleboards (WFP), like other wood-based items, require the addition of fire retardants (FRs) to reduce their high flammability. In this work, a waste lignosulfonate (CaLS) from paper mill is used as a low-cost FR to reduce WFP flammability. CaLS is purified by dialysis and the dialysed lignosulfonate (LD) is used, alone or combined with ammonium polyphosphate (APP), as a FR additive in the preparation of urea-formaldehyde WFP. The fire behaviour of the modified WFPs is studied by cone calorimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The challenge in developing FR biocomposites is how to maintain mechanical strength performance [ 132 ]. Furthermore, the usage of FRs raises the cost of the finished product [ 133 ]. Halogen-based FRs and nano-sized FRs have been known to advance the flame retardancy of composite even at lower concentrations compared to metal hydroxide compounds.…”
Section: Potentialmentioning
confidence: 99%
“…The challenge in developing FR biocomposites is how to maintain mechanical strength performance [ 132 ]. Furthermore, the usage of FRs raises the cost of the finished product [ 133 ]. Halogen-based FRs and nano-sized FRs have been known to advance the flame retardancy of composite even at lower concentrations compared to metal hydroxide compounds.…”
Section: Potentialmentioning
confidence: 99%
“…However, research has also shown that LS purified by dialysis can act as fire retardants in wood flour-based particleboards by increasing char formation. 58 Whether LS can also improve fire safety for fertilizers should be subject to further research.…”
Section: Screening For Plasticizers and Anti-dust Propertiesmentioning
confidence: 99%
“…The rest is sold as a byproduct for fuel or as a mixture or binder in animal feed (Windeisen and Wegener 2012;Yang et al 2015;Zhang et al 2013). One attempt to make use of lignin-containing wastewater is to use it as a wood adhesive or reacting it with bisulfite to produce a lignosulfonate compound that is widely known as an additive in cement, fertilizer, paper coating, and others (Angelini et al 2019;Aro and Fatehi 2017;Hemmilä et al 2019). Thus the bioethanol production process from lignocellulosic materials is expected to produce minimal waste (zero waste) as the wastes are also processed further not to pollute the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Plasticizers, such as water-soluble lignosulfonates, are often added into the concrete mixture to disperse cement particles to enhance flow-properties while using low water contents (Childs et al 2019;Gupta et al 2017) Lignin consists of molecules of polyphenol compounds that serve as a binding of cells to each other so that it becomes stiff and rigid, but it can reduce its mechanical strength (Tribot et al 2019). Therefore, lignin can be used as adhesive in plywood, composites, and lignosulfonate (Angelini et al 2019;Aro and Fatehi 2017;Hemmilä et al 2019). Lignosulfonate is one of the lignin derivative obtained by sulfonation of lignin, a water-soluble polymer polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%